Theoretical analysis and development of a mechanism with punching device for transplanting potted vegetable seedlings - Zhou, Maile; Shan, Yiyin; Xue, Xianglei; Yin, Daqing (International Journal of Agricultural and Biological Engineering, 2020)
Several studies have indicated that potted vegetable seedling transplanting technology can greatly improve the ability of vegetable seedlings to resist cold, flood, drought, saline-alkali and pests. The existing transplanting equipment mostly adopts mechanical, electrical and hydraulic integration technologies with a complex structure and a high cost. To address the problems of the complex structure and low efficiency of existing transplanting equipment, a rotary transplanting mechanism for potted vegetable seedlings was developed through configuration analysis and optimization design. Through kinematic analysis of the transplanting mechanism, optimization design software was developed, and the parameters were optimized. A mechanism was developed for picking, transporting, hole punching and transplanting potted vegetable seedlings. The virtual simulation results showed that the maximum error of attitudes of the transplanting arm is less than 1.19° and that of the hole punching shovel is less than 1.7°. In this study, perforation, seedling harvesting and transplanting experiments were conducted through a bench test. The results showed that the specific trajectory and attitude of the potted vegetable seedlings transplanting mechanism conformed to the requirements of potted vegetable seedling transplantation and the success rate of seedling picking was 92.4%, which verified the correctness and feasibility of the rotary potted vegetable seedling transplanting mechanism. Keywords: planting machinery, transplanting mechanism, potted vegetable seedling, punching device, trajectory and attitude DOI: 10.25165/j.ijabe.20201304.5404 Citation: Zhou M L, Shan Y Y, Xue X L, Yin D Q. Theoretical analysis and development of a mechanism with punching device for transplanting potted vegetable seedlings. Int J Agric & Biol Eng, 2020; 13(4): 85–92.